ASSEMBLY BILL NO. 13 AN ACT TO ADD SECTION 6404.5 TO THE LABOR CODE, RELATING TO OCCUPATIONAL SAFETY AND HEALTH - ARCHIEHUDSON; BATES; CALDERA; EASTIN; FRIEDMAN,T; GOTCH; ISENBERG; KLEHS; MARGOLIN; PETRIS; SOLIS; TORRES; WATSON (Tufts Archival Research Center, 2007)
California legislature bill restricting workplace smoking. Lists exceptions to restriction. Preempts local ordinances. Specifies punishments of not adhering to the law.